Improvvisare aiuta ad abitare felicemente - Goldoni, Daniele (Scenari, 2021)
In many respects jazz has been associated with social forms of freedom or liberation: between the two World Wars, during the Beat Generation season, in the Sixties in the USA as well in Europe, and in black music. Freedom or liberation: in what ways, and for whom? While black and 1960s improvisation was the expression of specific communities, today jazz is understood above all as “art music” (or Classical American Music). Art, in a modern sense, does not have a “community”, understood as a “people”, but rather a “public”. When musicology or philosophy deal with jazz and improvisation by focusing mainly on “artistic” formal aspects – like the use of innovative language or rules – they fail to acknowledge the current lack of a connection between music and a “people”. However, music always expresses a “form of life” (Wittgenstein). I suggest some ideas for an “ethnography” of improvisation in the context of contemporary Western music, and, starting from some ideas of Cornelius Cardew, outline some improvisation practices that might help us to recognize our own form of life and place, and to more happily experience them.